Uganda Schistosomiasis Symposium 2023: understanding morbidity drivers and developing controlled human infection models for vaccine research - Egesa, Moses; Kiberu, Davis; Sanya, Richard E.; Alabi, Ayodele; Baluku, Joseph Baruch; Oguttu, David W.; Driciru, Emmanuella; Odongo, Matthew; Elliott, Alison M.; Walusimbi, Bridgious; Nkurunungi, Gyaviira (Trends in Parasitology, 2023)
Schistosomiasis impacts African populations most strongly. Despite Uganda’s leading role in the Schistosomiasis Control Initiative for mass drug administration (MDA), about half the population remains at risk and a quarter infected. Prevalence and intensity remain high, and morbidity severe, in northwest Uganda around Lake Albert and the Albert Nile. An effective vaccine could combat repeated infection following MDA, and controlled human infection (CHI) studies could enable such vaccine development. Therefore, the Uganda Schistosomiasis Multidisciplinary Research Center and CHI-in-Africa Network hosted a symposium in Uganda bringing together local and international partners to discuss research on the drivers of schistosomal morbidity and the development of CHI studies for helminth vaccine development in Africa. In this TrendsTalk, we invited 10 early- to mid-career researchers to summarise the symposium proceedings.
Keywords: Vaccine research; Human infection models; Schistosomiasis